The Performance of Malaysian Conventional and Islamic Unit Trust: Market Timing and Persistence - Khor, Soh Chiew (2010)
This research concludes that the respective performances evaluation of conventional and Islamic unit trust in Malaysia for the period of February 1995- July 2009 in four parts: (1) risk-adjusted return of unit trust (2) market timing abilities (3) selection performance and (4) persistence. Both Jensen‟s measure and Treynor-Mazuy regression analysis provide reasonable evidence to support the findings of the unit trust performances. This study highlights that the returns of the conventional and Islamic unit trust has outperformed the market throughout Feb 1995 to Jul 2009. Strategic market timing with right assessment of market conditions can be a tactic for the unit trust managers to obtain superior performance. In addition of that, an attempt is made to answer the question of whether past performance can be used to predict future performance of the unit trust. In general, the behaviour of Islamic unit trust does not differ from the conventional unit trust, nonetheless this study realize that Islamic unit trust is the best hedging investment against the economic recession compare to conventional. In summary, this study evaluates the effect of unit trust performance have important implications for investors, fund managers and unit trust regulatory in Malaysia for more efficient future decision making of the unit trust investing.